2020
DOI: 10.4103/jmu.jmu_13_20
|View full text |Cite
|
Sign up to set email alerts
|

Influence of breast density on patient's compliance during ultrasound examination: Conventional handheld breast ultrasound compared to automated breast ultrasound

Abstract: Background: Our aim was to study the influence of breast density on patient's compliance during conventional handheld breast ultrasound (US) or automated breast US (ABUS), which could be used as adjunct screening modalities. Methods: Between January 2019 and June 2019, 221 patients (mean age: 53; age range: 24–89 years) underwent both US and ABUS. All participants had independently interpreted US and ABUS regarding patient compliance. The diagnostic experience with US o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Although patient discomfort has been noted in previous studies, ABUS has been identi ed as a good alternative to HHUS (10,16). The main cause of discomfort observed in this study was pain during the examination, which is similar to the results of a previous study (17). This increased pain is related to the methods of administration of ABUS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although patient discomfort has been noted in previous studies, ABUS has been identi ed as a good alternative to HHUS (10,16). The main cause of discomfort observed in this study was pain during the examination, which is similar to the results of a previous study (17). This increased pain is related to the methods of administration of ABUS.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, younger patients tended to be less satis ed with ABUS. In contrast, an ABUS compliance study by De Giorgis et al reported that older people (> 40 years) showed a decrease in compliance (17). Arguably, it is known that the breast density tends to be higher in young women, and patients with denser breasts feel more pain when the breast is compressed, whereas women with small breasts experience pain because of di culty under pressure (16).…”
Section: Discussionmentioning
confidence: 99%